Antitumoral effect of local injection of TLR-9 agonist emulsified in Lipiodol with systemic anti-PD-1 in a murine model of colorectal carcinoma - Grindel, Anne-Laure; Fretellier, Nathalie; Soares, Miguel; Bouzakher, Nabiha; Millot Maysounabe, Vincent; Santus, Robin; Bawa, Olivia; Wintrebert, Melody; Couquelet, Clémence; Robert, Philippe; Emile, Jean-Francois; Capron, Claude (Frontiers in Immunology, 2024)
Introduction Local treatments of cancer, including transarterial chemoembolization, could enhance responses to systemic immune checkpoint inhibitors such as anti-PD-1 antibodies. Lipiodol, a radiopaque oil, is widely used for transarterial chemoembolization as a tumor-targeting drug carrier and could be used in emulsion with immunomodulators. This study aimed at evaluating the antitumoral effect of intra-tumoral injection of Lipiodol-immunomodulator emulsions combined with systemic anti-PD-1 therapy in a murine model of colorectal carcinoma. Method Mice (male BALB/c) with anti-PD-1-resistant subcutaneous CT26 tumors were injected with immunomodulators, emulsified or not with Lipiodol (N=10-12/group). Results The TLR-9 agonist CpG displayed antitumor effects, while Poly I:C and QS21 did not. The Lipiodol-CpG emulsion appeared to be stable and maintained CpG within tumors for a longer time. Repeated intra-tumoral injections, combined with anti-PD-1, induced responses towards the tumor as well as to a distant metastatic-like nodule. This treatment was associated with an increase in proliferative CD8+ T cells and of IFN-γ expression, a decrease in proliferative regulatory T cells but also, surprisingly, an increase in myeloid derived suppressor cells. Conclusions Local administration of CpG emulsified with Lipiodol led to an effective antitumoral effect when combined to systemic anti-PD-1 therapy. Lipiodol, apart from its radiopaque properties, is an efficient drug-delivery system. The formulated oil-in-water emulsion allows efficient loading and control release of CpG, which induces favorable immune modifications in this murine tumor model.